The Prevalence of Non-infectious Diseases Among Overseas Chinese Workers in 2018 - Zhang, Bolin; Ye, Xiangguang; Chen, Qi; Jiang, Qinqin; Zhang, Xueying; Tong, Lian (Frontiers in Epidemiology, 2022)
Background: With the “Belt and Road” initiative, more Chinese citizens have gone abroad to engage in overseas labor activities. Few studies have investigated the prevalence of non-infectious diseases among Chinese overseas workers. This study seeks to fill the gap and illustrate the relevant diseases in a population of Chinese overseas workers. Methods: The health records of 13,529 Chinese migrant workers (12,917 males, mean age 41.3±8.7 years, and 612 females, mean age 33.1 ± 10.2 years) who visited the International Travel Health Care Center in Anhui province were obtained. Chi-square test and binary logistic regression models were used to analyze the associations between the prevalence of non-infectious diseases and sex , as well as the association between non-infectious diseases and length of stay abroad. Results: In this study, 34.6% of overseas workers were found to have one or more types of non-infectious diseases. Hypertension had the highest prevalence (9.58%). Hypertension, fatty liver, renal disease and abnormal liver function tests were more prevalent among male workers than among female workers, while anemia and abnormal urinalysis were more prevalent among female workers. The prevalence of hypertension, renal diseases, liver diseases and gallbladder diseases increased with the length of stay abroad. Conclusion: Non-infectious diseases including cardiovascular diseases, diabetes, and chronic respiratory diseases were highly prevalent among Chinese overseas workers. Hence the monitoring of non-infectious diseases needs to be enhanced to reduce China's overall disease burden in the future.